Synthesis and characterization of DSSC by using Pt nano-counter electrode: photosensor applications - Yahia, I. S.; AlFaify, S.; Al-ghamdi, Attieh A.; Hafez, Hoda S.; El-Bashir, S.; Al-Bassam, A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2016)
Pt electrode prepared by chemical method has been employed as counter electrode in dye-sensitized solar cell. TiO2 nanomaterial was deposited on fluorine-doped tin oxide substrate to be used as photoanode. Structure of the TiO2 and Pt films was investigated by atomic force microscope. The effect of illumination intensity on the photovoltaic parameters such as open circuit voltage, short circuit current density, output power, fill factor and efficiency of these cells was investigated in the range 2.5-130 mW/cm(-2). The cell efficiency is stable above 70 mW/cm(2). The fill factor is almost constant all over the studied range of illumination intensity. Impedance spectroscopy of the studied device as the summary measurements of the capacitance-voltage, conductance-voltage and series resistance-voltage characteristics were investigated in a wide range of frequencies (5 kHz-1 MHz). At low frequencies, the capacitance has positive values with peak around the origin due to the interfaces. At 200 and 300 kHz, the capacitance is inverted to negative with further increasing of the positive biasing voltage. Above 400 kHz, C-V profile shows complete negative behavior. Also, the impedance-voltage and phase-voltage characteristics were investigated. This cell shows a new promising device for photosensor applications due to high sensitivity in low and high illuminations.
Keywords: Photovoltaic Properties; Dye; Spectroscopy; Performance